Pengaruh Inflasi Domestik dan Utang Luar Negeri terhadap Nilai Tukar Rupiah - Cut Endang Kurniasih; Dahlan Tampubolon (Jurusan Ilmu Ekonomi dan Studi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Lambung, 2022)
Indonesia is a country that carries an open economy. Various internal and external factors will contribute to influencing the changes in the exchange rate at the same time. The purpose of this study is to investigate the impact of domestic inflation and external debt on the Rupiah exchange rate using secondary data from 2010.Q1 to 2021.Q1. Autoregressive Distributed Lag Analysis was used to analyze the data (ARDL). The study's findings confirmed the existence of a significant long-term relationship between the examined variables based on the analysis. It was found that both domestic inflation and external debt have a positive and significant effect on the Rupiah exchange rate over the long run, according to the long-run estimation results. Further, domestic inflation positively impacts the Rupiah exchange rate in the short-term estimation results, whereas external debt has a negative effect. Based on these findings, the government should maintain control over monetary variables such as inflation and the exchange rate through appropriate monetary policies and ensure that all external debt is prudently managed and directed toward more productive uses to mitigate exchange rate risk.